Detection of a new bla OXA-51-Like variant (bla OXA-1328 ) and a novel sequence type (ST3457/2790) in Acinetobacter baumannii isolated from community sewage and an incinerator surface in Nigeria - Khalifa Jamil Saleh; Muhammad Yusha’u; Abdullahi Hassan Kawo; Evelyn Skiebe; Gottfried Wilharm; Ibrahim Yusuf (BMC Research Notes)
Abstract Objectives Acinetobacter baumannii is an opportunistic pathogen with a high capacity to acquire antimicrobial resistance determinants, including OXA-type β-lactamases, which confer resistance to carbapenems. Environmental reservoirs play a crucial role in the persistence and spread of the bacteria; yet, limited data exist on variants of A. baumannii from non-hospital environments; an area critical to epidemiological studies in Nigeria. This study aimed to investigate the genetic diversity of A. baumannii strains from different non-hospital environments in Nigeria, determine their sequence types, and characterize their resistance genes. Results In the course of investigating the prevalence of A. baumannii in 440 environmental samples of soil, sewage, water, and air, collected from three non-hospital communities in Nigeria, isolates with novel features were discovered. Using culture-based and molecular identification, 33 isolates which is equivalent to 7.5% were confirmed as A. baumannii. Whole-genome sequencing of three A. baumannii isolates revealed novel genetic features: isolate S6, obtained from community sewage, harbored a novel bla OXA-51-like variant, bla OXA-1328 , which diverges from bla OXA-180 variants previously detected in Nigerian soil environments; isolate S5, recovered from an incinerator surface, carried a new sequence type, ST3457/2790; and isolate S4, from semi-pristine soil, harbored the rare variant bla OXA-707 , previously reported only once in a stork bird from Poland. The three isolates were highly susceptible to imipenem, meropenem, ceftazidime, sulfamethoxazole, piperacillin–tazobactam, ampicillin–sulbactam, ciprofloxacin, and 100% resistant to ceftriaxone. An intermediate susceptibility to colistin was observed in all isolates. The strain isolated from an incinerator surface clustered with strains recovered from human oral sources in China, suggesting a potential link to clinical strains.